Potato Starch-sodium Alginate-Zr (IV) Phosphate Bio-nanocomposite Ion Exchanger: Synthesis, Characterization and Environmental Application - War, Jahangir A.; Chisti, Hamida- Tun-Nisa (Current Analytical Chemistry, 2022)
Background: The introduction of inorganic fillers into the polymer matrix (with multiplicity in functionalization) augments the specific properties of such materials. One such method employed here, which is environmental friendly and facile is the sol-gel synthesis Objective: The nanocomposite synthesized by the above-mentioned method was primarily utilized for ion-exchange applications in general and cation exchange in particular. The ZrP based nanocomposite (PS/AG/ZrP) has been examined (as a photocatalyst) for the elimination of toxic cationic dye, methylene blue (Mb) from the wastewater by the mechanism of photodegradation. This study provides the experimental evidence and discussion of the different physicochemical characteristics of the synthesized nanocomposite. Methods: Herein, we synthesized zirconium phosphate (ZrP)-linked-potato starch/sodium alginate nanocomposite ion exchanger (PS/AG/ZrP) employing facile sol-gel method. Highly sophisticated techniques like FTIR, TGA, SEM, TEM, XRD & UV-Vis were subjected to characterize the PS/AG/ZrP nanocomposite Results: The ion exchange (IE) results show that the nanocomposite ion exchanger (PS/AG/ZrP-6) exhibited higher IEC (2.1meq/g) and thermal stability as conferred from IEC and TGA studies. Using UV-Vis irradiation, photocatalytic results revealed that 74.5% of Mb dye was degraded by novel nanocomposite (PS/AG/ZrP) within 50 minutes Conclusion: The results discussed reveal that the nanocomposite (PS/AG/ZrP-6) is a potential candidate for ion exchange applications vis-à-vis a photocatalyst for the remediation of wastewater as the time demands. The nanocomposite (PS/AG/ZrP-6) successfully characterized through various techniques and utilized as a potential ion exchanger and a photocatalyst for the dye degradation (MB) under UV-Vis irradiation.
Keywords: ion exchanger